Sexual dimorphism of vertical bar patterning in the South European toothcarp Aphanius fasciatus. Issue 5 (3rd May 2013) - Cavraro, F.; Zucchetta, M.; Torricelli, P.; Malavasi, S.
<x xml:space="preserve">Abstract</x> Sexual dimorphism of vertical bar patterning along the ontogenetic gradient was investigated in the South European toothcarp Aphanius fasciatus through the analysis of field samples collected from four different Venice Lagoon sites. Results suggested that, after controlling for site effect, vertical bar number and density were more correlated with size in females than in males, yielding a higher number of less spaced bars in females than in males. Results are discussed with regard to the interplay between natural and sexual selection acting on vertical bar dimorphism, suggesting a role of disruptive colouration in females and a more pronounced role of sexual selection in males.